Sepsis and infection: Two words that should not be confused - Vincent, Jean-Louis (Frontiers in Medicine, 2023)
The underlying cause of sepsis is a dysregulated host response to infection, leading to multiple organ failure. Identifying sepsis is crucial because of the associated pathophysiological, practical, and therapeutic implications, which will determine where and how the patient should be managed. In the absence of an end-of-life decision to limit therapies, the patient should be admitted to the intensive care unit immediately. Importantly, not all patients with sepsis are the same and being able to better characterize them is important. The future will focus on phenotypes to characterize critically ill patients, with or without infection, to enable more appropriate targeting of therapeutic interventions.